1987
DOI: 10.1002/macp.1987.021880502
|View full text |Cite
|
Sign up to set email alerts
|

Acid and base functionalization of ethylene‐propylene rubbers, 1. Grafting of tertiary amino groups and “interpolymer” network formation

Abstract: Base functionalization of saturated ethylene-propylene rubbers (EPR) was performed either by means of the radical grafting of 2-(dimethylamino)ethyl methacrylate onto EPR or by the reaction of a succinic anhydride grafted EPR with N,N-dimethylethylenediamine. Differences in the structure of the grafted molecules and in their thermal stability are also reported. An investigation is made on the reactivity of EPR having tertiary amino pendant groups toward acid functionalized EPR leading to gelation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Freeradical grafting should be a viable route also for reactions in solution, although no examples are reported with a maleimide derivative as the monomer. A procedure frequently found involves the post-modification of maleated polyolefins with an amine or amine-terminated macromolecule [45,46]. However, such approach is likely to lead to lower grafting yields, and therefore to less efficient use of the aminofunctional derivative.…”
Section: Polyolefin Fluorination Through Free-radical Grafting Of Flumentioning
confidence: 99%
“…Freeradical grafting should be a viable route also for reactions in solution, although no examples are reported with a maleimide derivative as the monomer. A procedure frequently found involves the post-modification of maleated polyolefins with an amine or amine-terminated macromolecule [45,46]. However, such approach is likely to lead to lower grafting yields, and therefore to less efficient use of the aminofunctional derivative.…”
Section: Polyolefin Fluorination Through Free-radical Grafting Of Flumentioning
confidence: 99%
“…O anidrido maleico (AM) tem sido utilizado para modificar diversos polímeros, como polietilenos [5,6] , polipropileno [7,8] , EPDM [9] , EPR [10] , eicosano e esqualano [11] e elastômeros [12] . A enxertia de AM pode ser realizada por diferentes métodos, como em solução [7] , em estado fundido [13] , em suspensão [12] e em estado sólido [14] .…”
Section: Influência Da Estrutura De Diferentesunclassified
“…In studies on reactive blending of polymers, it became clear that, although there are several commercially available polymers containing acidic functionalities, few commodity or engineering polymers with basic functionalities are available. Attempts to make nucleophilic or basic functionalized polymers have successfully resulted in polyolefins grafted with a tertiary [12][13][14][15] amine, 2-dimethylamino ethyl methacrylate (DMAEMA) , or a second-aryI6 amine, t-butylamino ethylmethacrylate (t-BAEMA) . A model study showed that secondary amino groups can form both ionic and covalent bonds, while tertiary amino groups can only form ionic bonds or polar interaction with polymers containing carboxylic acid or maleic anhydride group^.…”
Section: Introductionmentioning
confidence: 99%